Hydrodynamic shear-based purification of cancer cells with enhanced tumorigenic potential. Issue 1 (21st January 2020) - Cermeño, Efraín A; O'Melia, Meghan J; Han, Woojin M; Veith, Austin; Barber, Graham; Huang, Emina H; Thomas, Susan N; García, Andrés J
Abstract: Tumor-initiating cells (TICs), a subpopulation of cancerous cells with high tumorigenic potential and stem-cell-like properties, drive tumor progression and are resistant to conventional therapies. Identification and isolation of TICs are limited by their low frequency and lack of robust markers. Here, we characterize the heterogeneous adhesive properties of a panel of human and murine cancer cells and demonstrate differences in adhesion strength among cells, which exhibit TIC properties and those that do not. These differences in adhesion strength were exploited to rapidly ( 10 min) and efficiently isolate cancerous cells with increased tumorigenic potential in a label-free manner by use of a microfluidic technology. Isolated murine and human cancer cells gave rise to larger tumors with increased growth rate and higher frequency in both immunocompetent and immunocompromised mice, respectively. This rapid and label-free TIC isolation technology has the potential to be a valuable tool for facilitating research into TIC biology and the development of more efficient diagnostics and cancer therapies.